2005
DOI: 10.1128/mcb.25.2.545-553.2005
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of p53 and MDM2 Activity by MTBP

Abstract: p53 is a critical coordinator of a wide range of stress responses. To facilitate a rapid response to stress, p53 is produced constitutively but is negatively regulated by MDM2. MDM2 can inhibit p53 in multiple independent ways: by binding to its transcription activation domain, inhibiting p53 acetylation, promoting nuclear export, and probably most importantly by promoting proteasomal degradation of p53. The latter is achieved via MDM2's E3 ubiquitin ligase activity harbored within the MDM2 RING finger domain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
69
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 45 publications
(49 reference statements)
6
69
2
Order By: Relevance
“…Because the Mtbp-null lethality was not rescued by loss of p53, and because Mtbp heterozygosity did not show any obvious effects on p53 activity in tumor development, we hypothesized that p53 activity was not increased in Mtbp þ /À heterozygous cells, in contrast to previously published in vitro data (Brady et al, 2005). To test this hypothesis, we compared p53 and Mdm2 protein levels in thymocytes between wild-type and Mtbp þ /À mice (Figure 2e).…”
Section: A Metastatic Tumor Phenotype In Mtbpcontrasting
confidence: 41%
See 2 more Smart Citations
“…Because the Mtbp-null lethality was not rescued by loss of p53, and because Mtbp heterozygosity did not show any obvious effects on p53 activity in tumor development, we hypothesized that p53 activity was not increased in Mtbp þ /À heterozygous cells, in contrast to previously published in vitro data (Brady et al, 2005). To test this hypothesis, we compared p53 and Mdm2 protein levels in thymocytes between wild-type and Mtbp þ /À mice (Figure 2e).…”
Section: A Metastatic Tumor Phenotype In Mtbpcontrasting
confidence: 41%
“…One study suggests that overexpression of MTBP causes G 1 arrest of cell cycle independent of p53 (Boyd et al, 2000). The other reported that MTBP decreases p53 activity via the stabilization of Mdm2 by protecting it from self-ubiquitination (Brady et al, 2005). Thus, MTBP is downstream of Mdm2 in a p53-independent manner, but is also an upstream regulator of Mdm2, leading to decreased p53 activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Overexpression of MTBP was shown to suppress cell proliferation and colony formation of several human cancer cell lines independent of their p53 status. 1 Brady et al 2 reported that overexpression of MTBP in MCF7 cells resulted in MDM2 stabilization and subsequent p53 degradation. However, our previous findings demonstrated that complete deletion of MTBP in mice resulted in an early embryonic lethal phenotype independent of p53.…”
mentioning
confidence: 99%
“…There are various regulatory mechanisms to modulate Mdm2 functions. Mdm2 enzymatic activity is inhibited by its association with p19 ARF [13], ribosomal protein L11 [14] or TSG101 [15], while enhanced by interacting with MTBP [16] or YY1 [17]. Post-translational modification, such as phosphorylation by Ataxia Telangiectasia-mutated (ATM) in response to DNA damage, also regulates Mdm2-p53 interaction [18].…”
mentioning
confidence: 99%